Androgen receptor expression in preputial dartos tissue correlates with physiological androgen exposure in congenital malformations of the penis and in controls. Issue 1 (February 2020) - Tack, L.J.W.; Praet, M.; Van Dorpe, J.; Haid, B.; Buelens, S.; Hoebeke, P.; Van Laecke, E.; Cools, M.; Spinoit, A.F.
Summary: Introduction: The androgen receptor (AR) plays an important role in the development of male genitalia, and impaired androgen signalling has been hypothesised to underlie congenital penile malformations (CPM) such as hypospadias. Previous studies exploring the role of AR expression in the development of CPM have yielded conflicting results. Objectives: To assess AR expression in human foreskin of boys/men born with hypospadias, buried penis versus controls. Study design: Foreskin samples of 428 boys and men undergoing primary penile surgery (198 controls, 197 hypospadias, and 33 buried penis) were collected between October 2013 and July 2018. AR staining was performed in all samples and semi-quantitatively scored by two researchers independently, using a modified quick score (mQuicks) that assesses the proportion and intensity of AR staining in smooth muscle fibres. Results: The interobserver variability of the mQuicks had a high level of agreement for the total score, as well as for the subscores. Two phases of high AR expression were observed in all groups, the first following the postnatal gonadotropin surge (i.e., mini-puberty) and the second in (pre-) puberty. No differences in AR expression were found in hypospadias or buried penis cases as compared to controls matched for age at time of surgery. Discussion: This study describes the physiological evolution in AR expression in the human foreskin of boys with CPM and explains the cause of the previously reported, conflicting results. Despite the very large cohort, the limitations of this study are the low number of cases younger than six months at the time of surgery and the lack of Tanner stages to correlate with the mQuicks in adolescents. Conclusions: The mQuicks is a straightforward and informative tool to semi-quantitatively assess AR expression in the dartos tissue. In this study, AR expression in human foreskin shows a bimodal distribution in boys with CMP and controls, following physiological androgen exposure. No statistically significant difference in AR expression could be found between both groups. Whether other local mechanisms are affected by these physiological changes is currently unclear. However, strict age-matching should be considered when exploring the mechanisms underlying disturbed penile and urethral development in CMP. Image 1